1998
DOI: 10.1002/(sici)1099-0496(199803)25:3<147::aid-ppul3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The anaerobic threshold in cystic fibrosis: Comparison of V-slope method, lactate turn points, and Conconi test

Abstract: Physical exercise can improve sputum clearance in patients with cystic fibrosis (CF). To set up individual training protocols it is desirable to know the anaerobic threshold (AT). Established methods such as blood lactate measurements and ergometry can only be performed in specialized centers. Conconi showed that the heart rate threshold (HRT), i.e., the deflection point from the linear relationship between work load and heart rate, correlated significantly with the AT in healthy adults. To assess the reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…15 However, a recent report showed the occurrence of a HR deflection point using Conconi's technique in only 17 of 32 (53%) patients with cystic fibro-sis who had mild to moderate pulmonary disease. 16 Moreover, when identified, HR deflection tended to overestimate AT. Schmid et al 17 recently reported that HR deflection also occurred in endurance trained paraplegics during arm cranking exercise, although no causal relation was found to the AT.…”
mentioning
confidence: 96%
“…15 However, a recent report showed the occurrence of a HR deflection point using Conconi's technique in only 17 of 32 (53%) patients with cystic fibro-sis who had mild to moderate pulmonary disease. 16 Moreover, when identified, HR deflection tended to overestimate AT. Schmid et al 17 recently reported that HR deflection also occurred in endurance trained paraplegics during arm cranking exercise, although no causal relation was found to the AT.…”
mentioning
confidence: 96%
“…Before the pre-testing first training session, each participant was tested by the Conconi test, a noninvasive method for assessing individual anaerobic thresholds by the heart rate threshold (i.e., deflection point from the linear relationship between work load and heart rate) [35]. The heart rate threshold has been shown to be correlated significantly with the anaerobic threshold in healthy individuals and later, it was shown to be applicable for evaluating the anaerobic threshold even in participants with certain health problems [36]. This protocol allowed us to determine the individual heart rate threshold for each participant, which was later used as an indicator of maximal individual training load.…”
Section: Physical Exercise Programsmentioning
confidence: 99%
“…40 This relationship was confirmed by several authors and working groups; [59][60][61][62][63][64] however, a great number of authors disagreed and have challenged the HRTP method for several reasons. [3][4][5][13][14][15]22,23,29,[65][66][67][68] The gold standard for the anaerobic threshold is the so-called maximal lactate steady state during constant load exercise of at least 20 min in duration. The HRTP has also compared with this standard.…”
Section: Relationship Of Hrtp and Ltp 2 Vt 2 Mlssmentioning
confidence: 99%